ИНФОРМАЛ ТӘЛИМ ТИЙКАРЫНДА ИНФОРМАТИКА ОҚЫТЫЎШЫЛАРЫНЫҢ ҚӘНИГЕЛИГИН АРТТЫРЫЎ МЕТОДИКАСЫ - Жолдасова, К.Ж. (FAN va JAMIYAT, 2024)
This article presents opinions and possibilities of the process of advanced training, as well as an analysis of the problem of developing the process of advanced training based on informal education.